Nilai Budaya Novel Memang Jodoh Karya Marah Rusli - Rachmasisca, Frieska Maryova (Lentera: Jurnal Ilmiah Kependidikan, 2017)
The problem in this research was related to the culture values existed in Marah Rusliâs Memang Jodoh. The result of this research shows that the culture value found in Marah Rusliâs Memang Jodoh are: about tradition, marriage and matchmaking, polygamy, and relationship in Minangkabau culture. With the setting of living custom and tradition in the past Minangkabau society, this novel can be the valuable source when we want to understand how the the Minangkabau tradition and culture influence the living society in the past time and, until now, it can be experienced eventhough it has been scraped by the age. The most interesting culture value in this novel is about the tradition of marriage and polygamy. Minangkabau society, at that time, had a rule that the marriage must be done with the internal Minangkabau society only (internal), it was forbiden to have marriage with someone came from out of Minang ethnic.